Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1088/0953-8984/26/44/445007
|View full text |Cite
|
Sign up to set email alerts
|

Height distribution of equipotential lines in a region confined by a rough conducting boundary

Abstract: Abstract.This work considers the behavior of the height distributions of the equipotential lines in a region confined by two interfaces: a cathode with an irregular interface and a distant flat anode.Both boundaries, which are maintained at distinct and constant potential values, are assumed to be conductors. The morphology of the cathode interface results from the deposit of 2 × 10 4 monolayers that are produced using a single competitive growth model based on the rules of the Restricted Solid on Solid and Ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…To overcome this difficulty, we developed an algorithm to round off the sharpest projections and replace the real WM surface with an equipotential surface, Φ E (very similar to the previous one), that is calculated from the numerical solution of the Laplace equation using a finite-difference scheme (Liebmann method - see Supplementary Information ). For practical applications, this approximation corresponds, for instance, to the condition in which good Spindt arrays 22 are produced by slowly increasing the voltage such that the sharpest tips “burn off.” Our numerical solution has been shown to yield an FEF for ideal protuberances that is in very good agreement with the results of previous analytical, finite-element and multigrid methods 23 24 25 .…”
Section: Morphology Of a Lacfessupporting
confidence: 84%
See 1 more Smart Citation
“…To overcome this difficulty, we developed an algorithm to round off the sharpest projections and replace the real WM surface with an equipotential surface, Φ E (very similar to the previous one), that is calculated from the numerical solution of the Laplace equation using a finite-difference scheme (Liebmann method - see Supplementary Information ). For practical applications, this approximation corresponds, for instance, to the condition in which good Spindt arrays 22 are produced by slowly increasing the voltage such that the sharpest tips “burn off.” Our numerical solution has been shown to yield an FEF for ideal protuberances that is in very good agreement with the results of previous analytical, finite-element and multigrid methods 23 24 25 .…”
Section: Morphology Of a Lacfessupporting
confidence: 84%
“…For practical applications, this approximation corresponds, for instance, to the condition in which good Spindt arrays [22] are produced by slowly increasing the voltage such that the sharpest tips "burn off." Our numerical solution has been shown to yield an FEF for ideal protuberances that is in very good agreement with the results of previous analytical, finite-element and multigrid methods [23][24][25].…”
Section: Morphology Of a Lacfessupporting
confidence: 84%
“…A related result was obtained in Ref. [43], where the profile statistics of equipotentials, which are akin to the output profile in SPM techniques, generated by self-affine conducting surfaces yield a large skewness for a growth model in the regime of the linear Edwards-Wilkinson universality class [7], for which S = 0.…”
Section: Spm Surfaces and The Kpz Classmentioning
confidence: 56%
“…For a fixed growth time, we observed that both skewness and kurtosis increase with the tip size, since the lowest height contributions are being depleted, but values consistent with KPZ (S=0.4 to 0.5 against 0.43 and K=0.3 to 0.5 against 0.35) are observed for R T comparable to ξ; see also discussion on figure 3 for time dependence. A related result was obtained in [43], where the profile statistics of equipotentials, which are akin to the output profile in SPM techniques, generated by self-affine conducting surfaces yield a large skewness for a growth model in the regime of the linear Edwards-Wilkinson universality class [7], for which S=0.…”
Section: Spm Surfaces and The Kpz Classmentioning
confidence: 78%